Possible role for nephron‐derived angiotensinogen in angiotensin‐II dependent hypertension. Issue 1 (12th January 2016) - Ramkumar, Nirupama; Stuart, Deborah; Calquin, Matias; Wang, Shuping; Niimura, Fumio; Matsusaka, Taiji; Kohan, Donald E.
Abstract: The role of intranephron angiotensinogen (AGT) in blood pressure (BP) regulation is not fully understood. Previous studies showed that proximal tubule‐specific overexpression of AGT increases BP, whereas proximal tubule‐specific deletion of AGT did not alter BP. The latter study may not have completely eliminated nephron AGT production; in addition, BP was only assessed on a normal salt diet. To evaluate this issue in greater detail, we developed mice with inducible nephron‐wide AGT deletion. Mice were generated which were hemizygous for the Pax8‐rtTA and LC‐1 transgenes and homozygous for loxP‐flanked AGT alleles to achieve nephron‐wide AGT disruption after doxycycline induction. Compared to controls, AGT knockout (KO) mice demonstrated markedly reduced renal AGT immunostaining, mRNA, and protein levels; unexpectedly AGT KO mice had reduced AGT mRNA levels in the liver along with 50% reduction in plasma AGT levels. BP was significantly lower in the AGT KO mice compared to controls fed a normal, low, or high Na + intake, with the highest BP reduction on a low Na + diet. Regardless of Na + intake, AGT KO mice had higher plasma renin concentration (PRC) and markedly reduced urinary AGT levels compared to controls. Following angiotensin‐II (Ang‐II) infusion, AGT KO mice demonstrated an attenuated hypertensive response despite similar suppression of PRC in the two groups. Taken together, these data suggest that nephron‐derived AGT may be involved in Ang‐II‐dependent hypertension, however, a clear role for nephron‐derived AGT in physiological BP regulation remains to be determined. Abstract : In this study, we demonstrate that nephron‐derived angiotensinogen may be involved in Ang‐II dependent hypertension and is the likely source for urinary angiotensinogen excretion. However, a clear role for nephron‐derived AGT in physiological BP regulation remains to be determined.